Generation of the current normal to the surface of the antenna by electromagnetic waves and its application in the highly responsive receiver - Dobrovolsky, V.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
Generation of the initial current normal to the surface of the antenna by electromagnetic waves has been considered. It has been shown that the angle of grazing (or sliding) for the wave with the electric vector in the plane normal to the surface varies the radiation resistance over a wide range. This property allows matching the radiation impedances and loads. Here, it has been proposed to use this property to create a highly sensitive radiation detector. In relation to this task, a model of the radiation detection of the input radiation signal by a direct quadratic detector in the stationary mode with the diode included as the load has been considered. The obtained results prove that a diode with a high differential resistance can effectively operate with the antenna. The rise of the resistance increases the detector response voltage, its responsivity, and decreases the receiver noise equivalent power. Improvement of these characteristics by orders of magnitude is possible. The considered mechanism allows detectors to operate in the infrared spectral range, and the increase in the wavelength, in principle, does not limit their functioning. Розглянуто генерування початкового струму, нормального до поверхні антени, електромагнітними хвилями. Показано, що кут ковзання (або падіння) хвилі з електричним вектором у площині, нормальній до поверхні, змінює опір випромінювання у широкому діапазоні його значень. Ця властивість дозволяє узгоджувати імпеданси випромінювання та навантаження. Пропонується використовувати цю властивість для створення високочутливого приймача випромінювання. У зв’язку з цим завданням побудовано модель детектування вхідного сигналу випромінювання квадратичним детектором прямого детектування в стаціонарному режимі з діодом, включеним як навантаження. Отримані результати доводять, що діод з високим диференціальним опором може ефективно працювати з антеною. Підвищення опору збільшує напругу відгуку детектора, його чутливість і зменшує еквівалентну шумову потужність приймача випромінювання. Можливе вдосконалення цих характеристик на порядки. Розглянутий механізм може бути застосований до детекторів інфрачервоного діапазону спектра, і збільшення довжини хвилі, в принципі, не обмежує його функціонування.